Self-respect and independence of mind the challenge of Fukuzawa Yukichi - Kitaoka, Shin'ichi 1948-; Vardaman, James M. 1947- (2017)
"It is said that Japan is currently experiencing its third opening to the outside world. However, in terms of importance, rather than the so-called second opening$1(Bwhich refers to the reforms following World War II$1(Bthe more significant opening was that of the Meiji Restoration, initiated and carried out by the Japanese themselves. Consequently, as Japan today finds itself feeling trapped with a sense of despair, it is to the Meiji era that we should turn, and more than to anyone else, the person we should turn to is Fukuzawa Yukichi. With the general reader in mind, this volume brings together the results of the present-day research into the accomplishments of Fukuzawa as part of an overall appraisal of the man himself"--Back cover.
Preface to the English edition -- Foreword -- The Nakatsu period -- Ogata's Tekijuku -- Going to America -- Learning about Europe -- Condition in the West -- Keio Gijuku -- An encouragement of learning -- An outline of a theory of civilization -- Leaders of Meiji restoration and Fukuzawa Yukichi -- "Discourse on the National Assembly" and the political crisis of 1881 -- Home and daily life -- The Korean issue -- Establishment of the cabinet system and treaty revision -- The early diet and the Sino-Japanese War -- Last years and death -- Notes -- Bibliography -- Fukuzawa chronology -- About the author.
Translation of: Dokuritsu jison : Fukuzawa Yukichi no chosen.
Includes bibliographical references (pages 322-324).
Japan Foundation
Text translated into English from Japanese.
Keywords: Fukuzawa, Yukichi -- 1835-1901.; Educators -- Japan -- Biography